Five views on the Exodus : historicity, chronology, and theological implications - Janzen Mark D.; Stripling, Scott; Hoffmeier, James Karl, 1951-; Feinman, Peter Douglas; Rendsburg, Gary; Hendel, Ronald S.; Janzen, Mark, 1980-; Gundry, Stanley N. (Grand Rapids : Zondervan, 2021)
"Five Views on the Exodus brings together experts in the fields of biblical studies, Egyptology, and archaeology to discuss and debate the most vexing questions about the Exodus"--
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Bible. -- Criticism, interpretation, etc; Exodus, The -- History of doctrines; Jews -- History -- To 1200 B.C.